MORPHOLOGICAL AND HISTOCHEMICAL CHANGES IN THE THYROID AND INTER-RENAL CELLS DURING BREEDING AND NON-BREEDING PERIODS OF CHANNA GACHUA (HAMILTON) - Mishra, S K (Indian Journal of Fisheries, 2011)
Thyroid and interrenal cells of Channagachua exhibit cyclic histological and histochemical changes during various phases of annual ovarian cycle revealing their inactivity and hyperactivity during non-breeding and breeding periods respectively. There is a direct correlation between the cyclic activity in the ovaries and the cyclic activity in the interrenal cells and thyroid